Dysautonomia in the Ehlers–Danlos syndromes and hypermobility spectrum disorders—With a focus on the postural tachycardia syndrome. Issue 4 (12th November 2021) - Mathias, Christopher J.; Owens, Andrew; Iodice, Valeria; Hakim, Alan
Abstract: Dysautonomia (autonomic dysfunction) occurs in the Ehlers–Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD). Symptoms include palpitations, dizziness, presyncope, and syncope, especially when standing upright. Symptoms of orthostatic intolerance are usually relieved by sitting or lying and may be exacerbated by stimuli in daily life that cause vasodilatation, such as food ingestion, exertion, and heat. Neurocardiovascular dysautonomia may result in postural tachycardia syndrome (PoTS), a major cause of orthostatic intolerance. It is defined by a rise in heart rate of >30 beats per minute (bpm) in adults and >40 bpm in teenagers while upright, without a fall in blood pressure (BP; orthostatic hypotension). In some, it can be compounded by the presence of low BP. For many, there is delay in clinicians recognizing the nature of the symptoms, and recognizing EDS or HSD, leading to delays in treatment. The onset of PoTS may be linked to an event such as infection, trauma, surgery, or stress. Gastrointestinal and urinary bladder involvement may occur, along with thermoregulatory dysfunction. In some, the mast cell activation syndrome may be contributary, especially if it causes vasodilatation. This paper reviews neurocardiovascular dysautonomia with an emphasis on PoTS, its characteristics, associations, pathophysiology, investigation, and treatment.